Penentuan Kelayakan Pemberian Bantuan BBM pada Nelayan menggunakan Metode Vikor : (Studi Kasus : Dinas Perikanan dan Kelautan Kabupaten Langkat) - Anisa Putri Pratiwi; Relita Buaton; Melda Pita Uli Sitompul (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
Fishermen is a term for people whose daily work is catching fish or other biota that live on the bottom or surface of the water. Fishermen can also discuss and share experiences in overcoming problems in the fisheries and marine sector to meet the needs of fishermen. The government of the Fisheries and Marine Service is required to support the need for subsidized fuel for fishermen. The increase in fuel oil (BBM) has an impact on the operational costs of fishermen, because BBM is one of the main components in the daily activities of fishermen, with the high price of BBM, fishermen will face an increase in operational costs that they must spend to carry out fishing activities. This can reduce the income earned by fishermen, because higher costs will affect the profits that fishermen get from the sale of fish. So the Fisheries and Marine Service of Langkat Regency Provides Assistance for Fishermen in Langkat Regency, from the many assistance that have been distributed in this thesis I took a sample of the Fishermen of Secanggang Village. Based on the research conducted, the results obtained were that the first alternative that was a priority to receive subsidized fuel assistance for fishermen in Langkat Regency with a Q value = 0 and was entitled to be recommended. And the next priority was the second alternative with a Q value = 0.492.